Design and development of multi-functional graphitic carbon nitride heterostructures embedded with copper and iron oxide nanoparticles as versatile sensing platforms for environmental and agricultural applications - Khasim, Syed; Pasha, Apsar; Dastager, Syed G.; Panneerselvam, Chellasamy; Hamdalla, Taymour A.; Al-Ghamdi, S. A.; Alfadhli, S.; Makandar, Mohammad Basha; Albalawi, Jalal Bassam; Darwish, A. A. A. (Ceramics International, 2023)
In the recent past, agrotechnology has witnessed a tremendous change due to the advent of technologies employed towards enhancing the yield and quality of the crops. The application of nanotechnology in agriculture is promoting sustainable practices and smart farming. Currently, nanomaterial-based sensors are gaining considerable attention in agrotechnology, such sensors can detect the environmental conditions and support for crop growth and enhances the agricultural yield. Graphiticcarbon nitride (g-C3N4), a soft polymer belongs to a class of 2-D semiconductors which are affordable, metal-free, indispensable for sensing applications due to significant changes in their conductivity upon exposure to analyte molecules in nano-regime. Further, this g-C3N4 can be combined with other nano metal oxides to form nanocomposites with remarkable properties and superior performance. In this work we report development of high-performance sensors based on graphitic carbon nitride embedded with copper and iron oxide nanoparticles. These heterostructures offers tremendous improvement in the physical and chemical properties due to the synergetic interactions between various phases. The chemiresistive sensor fabricated from these nanocomposites exhibit excellent sensitivity towards monitoring methane gas @ ppb level, relative humidity (% RH), and soil moisture content. Owing to their excellent sensitivity, stability and selectivity, this graphitic carbon nitride embedded with Cu and Fe oxide nanoparticles could be potentially used as multifunctional sensors towards environmental monitoring and greenhouse conditions in agricultural applications.
Keywords: Agricultural sensors; CuO nanoparticles; Environmental monitoring; FeO nanoparticles; Graphitic carbon nitride